Gambaran pengetahuan, sikap, dan tindakan masyarakat tentang pencegahan demam berdarah dengue di Kelurahan Paniki Bawah Kota Manado - Darren Liono Smith; Dina Victoria Rombot; Ronald Imanuel Ottay (Jurnal Kedokteran Komunitas dan Tropik, 2026)
Background: Dengue fever (DF) is one of the endemic diseases in Indonesia and remains a significant public health problem. Based on data from the Manado City Health Office, in 2024 there were 126 cases of dengue fever in Paniki Bawah Village. This number of cases is the highest of all recorded health centers. Aim: To describe the knowledge, attitudes, and actions of the community in Paniki Bawah Village regarding the prevention of dengue fever. Methods: This study used a quantitative descriptive design with a cross-sectional approach. The sample consisted of 109 respondents selected using proportional quota sampling. Data were collected using questionnaires and analyzed using univariate analysis. Results: The results showed that most respondents had good knowledge (60.6%), good attitudes (69.7%), and good preventive actions (75.2%). Conclusion: The community in Paniki Bawah Village has good knowledge, attitudes, and actions in preventing dengue fever.